Hubungan Antara Pola Asuh Dengan Status Gizi Pada Balita Usia 2-5 Tahun - Siwi, Sinta Arianti; , dr. Mohammad Shoim Dasuki, M. Kes; , dr. Anika Candrasari, M.Kes (2015)
Background: Nutrition is the important thing that can influence the growth and development of children. Based on Profil Kesehatan Jawa Tengah data on 2012 showed the percentage of the children have nutrition for less status are 4,88% and malnutrition status are 1.131 (0,06%). One of the indirect factors that influence the nutritional status is parenting. On the sanitation aspek, Surakarta reaches 92 %. Meanwhile one the prevention disease, reach 85% nationally. Objective: This study aim to analyze the correlation between parenting and nutritional status of 2 up to 5 years children in Posyandu Abadi 9 Gonilan Surakarta. Method: This research is an analytic observational research using cross- sectional approach. The samples are 30 sample children and 30 their mothers which fulfilled the inclusion criteria taken using purposive sampling method by measure the weight and height of the children and questionnaire to their mothers. Results: Based on the chi - square test and then it continues with fisher exact test from SPPS 17.0 for windows, p value on weight of age indicator is 0,584 and height of age is 0,431 which means there is no correlation between parenting and nutritional status of 2 up to 5 years children. Conclusion: There is no correlation between parenting and nutritional status of 2 up to 5 years children.